Oil and gas sources in Shunbei Oilfield, Tarim Basin - Rong GU; Lu YUN; Xiuxiang ZHU; Meng ZHU (Shiyou shiyan dizhi, 2020)
The hydrocarbon sources in the Middle and Lower Ordovician in the Shunbei area of the Tarim Basin were studied based on the geochemical characteristics of oil and gas samples. The saturated hydrocarbon gas chromatography, mass spectrometry of crude oil and natural gas, and the carbon isotope distribution of whole oil and group components were used. The C23 tricyclic terpane is dominant in crude oil samples from the Shunbei area, with a low content of gammacerane. The C27-C28-C29ααα20R regular steranes show an irregular "V" shape distribution. The regular steranes account for a larger amount than the rearranged steranes, and the carbon isotope of the crude oils is light. The geochemical characteristics of crude oil samples from the Middle and Lower Ordovician in the Shunbei area have a good affinity with those from the Lower Cambrian in the Keping outcrop and the well KT1. The δ13C1 and δ13C2 values of natural gas samples are -50.7‰ to -44.7‰ and -36.1‰ to -33.1‰, respectively. The gas dryness coefficient ranges from 0.520 to 0.883. The oil and natural gas in the Shunbei Oilfield have the same source, that is, the Lower Cambrian source rocks. The distribution of source rocks in the Lower Cambrian of the Tarim Basin was predicted by means of drilled lithofacies, sedimentary facies and seismic facies of the whole basin. The source rocks are about 30 m thick. They have a high TOC content and show a great hydrocarbon generation potential. They have experienced a long term of hydrocarbon generation and multiple stages of hydrocarbon supply, providing significant oil and gas resources for the Tarim Basin.